Cambridge preparation for the TOEFL test - Gear, Jolene; Gear, Robert; Lê Huy Lâm (Tp.HCM : Nxb Tp.HCM, 2002)
Listening; Structure; Reading; Writing.
Keywords: English language; Toefl; English language -- Tests; English language -- Study and teaching -- Textbooks for foreign speakers